Participatory management of human resources Exceed the value of human beings? - Melouki, Slimane (Université de M'sila, 2018)
If Human Resource Management is the management of the workforce organizations or human resources .The attracting staff, and selection , training, evaluation and reward employees, and also follow the leadership of the organization and the organizational culture and ensure compliance with labor laws .All of these components are willing to conduct collective negotiations , the initial role about a communication with staff representatives. Human resources personnel formers total workforce organization, or business sector or economy. Some used the term human capital in tandem with human resources, in spite of human capital usually refers to a narrower point of view, there are other terms are sometimes used include «workforce» or talent or «work» or just «individuals». And found human resources as a product of the human relations movement in the early twentieth century, when researchers began documenting ways to create values for the business through the strategic management of the workforce. Human resources were dominant work procedural daily, such as salaries and management benefits. This article aims to clarify the great position ofhuman resource functions In larger organizations, a whole section in the habit specialist and a staff specialists in various fields involved in strategic decision-making with the rest of the sections.
Keywords: Human Resource Management, Leadership,making Decision, organizational culture, training and the developing skills ,Innovation.